Specific Rhizobacteria Responsible in the Rhizosheath System of Kengyilia hirsuta - Chen, Youjun; Chen, Chen; Zhou, Qingping; Hu, Jian; Lei, Yingxia; Liu, Wenhui (Frontiers in Plant Science, 2022)
The rhizosheath is a critical interface supporting the exchange of resources between plants and their associated environment of soil. Favorable microenvironment of rhizosphere soil provides the rhizosheath formed and then promotes desert plant survival. However, it remains unclear how rhizosheath benefits the colonization of pioneer plants in alpine desert under changing environment. Here, we investigated the effect of different soil moisture and sterilization treatments (three moisture levels and unsterilized or sterilized soil) on rhizosheath forming process of Kengyilia hirsuta, a sand-inhabiting and drought-resistant pioneer plant of the Tibetan Plateau desert. The results showed that in both unsterilized and sterilized soil, increasing soil moisture first increased and then decreased rhizosheath weight, with the highest value is 25%. During rhizosheath formation, developing rhizosheaths were selectively enriched in the bacterial genera Massilia and Arthrobacter. These suggest the existence of a highly specialized signal recognition system during rhizosheath formation that involves the accumulation of bacteria. These bacterial species exhibited different roles in the process of rhizosheath formation and is an advantageous strategy for K. hirsuta.